Análise do comportamento de escavação grampeada instrumentada - Pereira Filho, André Luiz Delmondes (2020)
In the design of soil-nailed walls, there is no standard guideline to be followed by designers. Thus, in the current practice, it is important to combine technical knowledge and experience. In addition to theoretical analysis in the design phase, it is of fundamental importance to evaluate the behavior of the structure with use of instrumentations and tests in constructive and service phases. Thus, the objective of this master’s research project is to analyse the behavior of a soil-nailed excavation built at Salvador, Bahia. The retaining structure in study presents variable excavation height between 7.7 and 14.8 m, with nail length equal to 6.0, 9.0 and 12.0 m. The geotechnical profile of the excavation is basically composed of intercalated layers of sandy silt and clayey silt with sand. Data from the project, execution and experimental field program, consisting of pullout tests and inclinometer monitoring, were made available for this research. Results of pullout tests were compared to correlations with NSPT, proposed for Brazilian soils. Stability analyses and numerical stress and strain analyses were performed in a software package of geotechnical applications. Stability analyses were developed with application of Allowable Stress Design (ASD) e Load and Resistance Factor Design (LRFD) concepts. Deformation of soil mass and forces mobilized in nails were obtained from numerical analyses. the horizontal displacements profile obtained from numerical analyses had a good fit when compared to the profile monitored by the reference inclinometer. The results showed that the magnitude of maximum displacements obtained was lower than values of theoretical predictions in international technical literature. Numerical models also adequately represented the distribution of tensile forces in nails. Maximum tensile forces obtained from numerical modeling were lower than those calculated using theoretical methods. The results of stability analyses indicated that partial safety factors recommended by BS 8006-2 (2011) lead to more conservative projects, when compared to the recommendations of Eurocode 7.